Droga Johna Henry’ego Newmana do uznania autorytetu papieża - Lisowska, Natasza (Annales Missiologici Posnanienses, 2023)
Newman’s way to conversion was made possible by his overcoming of his youthful convictions adopted from Protestant theologians (Luther, Cranmer, Bale, Fox, Sandys, Warburton, Isaac, and Thomas Newton), that the office of the pope was related to the case of the Antichrist. Their accusation is summed up in the statement that the pope, by enacting and enforcing ecclesiastical laws, has obscured the true primary meaning of God’s commandments and has thus established himself in the place of God, making himself the master of Catholic consciences. Newman’s idea of the Antichrist evolved from associating him with the place and the office of the pope to recognizing only his hallmarks as significant: open infidelity, ungodlieness, arrogance, worldly spirit, and false liberalism. At the same time, he took a futuristic position, not excluding the view that the “secret of godlessness” is already at work, and the Antichrist has his precursors, types, images and shadows. He overcame the mental flaw that identified the pope with the Antichrist through in-depth studies of the history of the Church, a change withwhich was signaled in A Letter to the Rev. Godfrey Faussett (1838), matured in an apology of the papacy in The Protestant Idea of Antichrist (1840) and led to the recognition of the pope as the true Vicar of Christ and Sacramentum Unitatis and the revocation of anti-Roman views in 1843, and again in 1845. Newman understood that the primacy of the pope is part of an evolving Catholic doctrine, and the pope has become the goal of prosecution because of his close resemblance to Christ, whom Satan is trying to imitate.